Ehmm... a degree in Serat Kayu? - New Sunday Times (2004)
The one degree course on offer that most puzzled students and became the butt of every meritocracy-related joke was the B. Sc Perhutanan (Industri Teknologi Serat Kayu) or, as it is fondly called, the "Serat Kayu degree".